2001
DOI: 10.1128/iai.69.9.5385-5394.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Endoprotease (PrpL) Encoded by a PvdS-Regulated Gene inPseudomonas aeruginosa

Abstract: The expression of many virulence factors in Pseudomonas aeruginosa is dependent upon environmental conditions, including iron levels, oxygen, temperature, and osmolarity. The virulence of P. aeruginosa PAO1 is influenced by the iron-and oxygen-regulated gene encoding the alternative sigma factor PvdS, which is regulated through the ferric uptake regulator (Fur). We observed that overexpression of PvdS in strain PAO1 and a ⌬pvdS::Gm mutant resulted in increased pyoverdine production and proteolytic activity com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(186 citation statements)
references
References 52 publications
3
183
0
Order By: Relevance
“…As previously reported by Purschke et al (2012), we observed a significant increase in the production of iron-regulated proteases by P. aeruginosa in coculture supernatants, including PrpL, PasP, AprA and a hypothetical protein zinc-protease, PA0572 (Supplementary Table S3) (Wilderman et al, 2001;Marquart et al, 2005). These proteins are known for their strong proteolytic activities, which are responsible for rupturing tight junctions in the epithelium, leading to tissue invasion and bacterial spreading (Azghani et al, 1993).…”
Section: Interspecies Competition Triggers Virulencesupporting
confidence: 61%
“…As previously reported by Purschke et al (2012), we observed a significant increase in the production of iron-regulated proteases by P. aeruginosa in coculture supernatants, including PrpL, PasP, AprA and a hypothetical protein zinc-protease, PA0572 (Supplementary Table S3) (Wilderman et al, 2001;Marquart et al, 2005). These proteins are known for their strong proteolytic activities, which are responsible for rupturing tight junctions in the epithelium, leading to tissue invasion and bacterial spreading (Azghani et al, 1993).…”
Section: Interspecies Competition Triggers Virulencesupporting
confidence: 61%
“…We excised the bands and identified the proteins by N-terminal sequence analysis. The 49-kDa band was identified as alkaline metalloprotease AprA (24), the 33-kDa band was identified as elastase LasB (4,31), and the 27-kDa band is the PrpL protease (65). To ensure that the increased amounts of proteases were due to Ca 2ϩ addition and not due to PO 4 3Ϫ limitation (by possible PO 4 3Ϫ precipitation as calcium phosphate), experiments were performed with various concentrations of Ca 2ϩ and PO 4 3Ϫ as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…A similar change was also found for the secretion of PrpL, an endoprotease which is regulated by PvdS and the QS system. It can hydrolyse casein, elastin and lactoferrin (Wilderman et al, 2001;Lamont et al, 2002;Ravel & Cornelis, 2003;ArevaloFerro et al, 2003). It seems that the secretion of both AprA and PrpL is very sensitive to oxygen concentration.…”
Section: Proteomic Analysis Of Extracellular Proteinsmentioning
confidence: 99%